Biocompatible Nanoparticles as a Platform for Enhancing Antitumor Efficacy of Cisplatin–Tetradrine Combination - Liu, Fangcen (Nanoscale Res Lett, 2021)
Combination therapy has been a standard strategy in the clinical tumor treatment. We have demonstrated that combination of Tetradrine (Tet) and Cisplatin (CDDP) presented a marked synergistic anticancer activity, but inevitable side effects limit their therapeutic concentration. Considering the different physicochemical and pharmacokinetic properties of the two drugs, we loaded them into a nanovehicle together by the improved double emulsion method. The nanoparticles (NPs) were prepared from the mixture of poly(ethyleneglycol)–polycaprolactone (PEG–PCL) and polycarprolactone (HO-PCL), so CDDP and Tet can be located into the NPs simultaneously, resulting in low interfering effect and high stability. Images from fluorescence microscope revealed the cellular uptake of both hydrophilic and hydrophobic agents delivered by the NPs. In vitro studies on different tumor cell lines and tumor tissue revealed increased tumor inhibition and apoptosis rates. As to the in vivo studies, superior antitumor efficacy and reduced side effects were observed in the NPs group. Furthermore, (18)FDG-PET/CT imaging demonstrated that NPs reduced metabolic activities of tumors more prominently. Our results suggest that PEG–PCL block copolymeric NPs could be a promising carrier for combined chemotherapy with solid efficacy and minor side effects. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s11671-021-03511-4.